The Management of Teachers and Educational Staff: Their Roles and Importance in Enhancing the Quality of Learning - Nasution, Rifa'i; Mutia Asmara , Devi Sunita; Luyao Xu (Yayasan Insan Cipta Medan, 2024)
The management of teachers and educational staff plays a crucial role in enhancing the quality of learning. Effective management of teachers and educational staff is essential for reinforcing the foundation of quality education by providing the necessary resources and support for educators to excel in their teaching. This research aims to explore the roles of teacher and educational staff management in delivering quality education, assess the competencies of teachers and educational staff in improving the quality of learning, and enhance learning quality through effective management. The study utilizes advanced research methods, employing a qualitative approach through a literature review from various relevant sources to examine the roles of teacher and educational staff management in improving the quality of education. Therefore, this research is expected to provide a deeper understanding of the roles and importance of teacher and educational staff management in enhancing the quality of learning.